2013
DOI: 10.3758/s13423-013-0472-6
|View full text |Cite
|
Sign up to set email alerts
|

Decay uncovered in nonverbal short-term memory

Abstract: Decay theory posits that memory traces gradually fade away over the passage of time unless actively rehearsed. Much recent work exploring verbal short-term memory has challenged this theory, but there does appear to be evidence for trace decay in nonverbal auditory shortterm memory. Numerous discrimination studies have reported a performance decline as the interval separating two tones is increased, consistent with a decay process. However, most of the tone comparison research can be explained in other ways, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 39 publications
2
25
1
Order By: Relevance
“…Similarly, evidence challenging temporal distinctivenessbut supporting trace decay -has been reported for abstract auditory short-term memory. Two recent studies of acoustical memory did not find any temporal isolation effects using a delayed two-tone comparison task, indicating that distinctiveness cannot explain the loss of auditory representations over the passage of time (McKeown & Mercer, 2012;Mercer & McKeown, 2014). Most recently, Mercer and McKeown (2014, Experiment 2) asked participants to compare two abstract complex tones varying in timbre.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, evidence challenging temporal distinctivenessbut supporting trace decay -has been reported for abstract auditory short-term memory. Two recent studies of acoustical memory did not find any temporal isolation effects using a delayed two-tone comparison task, indicating that distinctiveness cannot explain the loss of auditory representations over the passage of time (McKeown & Mercer, 2012;Mercer & McKeown, 2014). Most recently, Mercer and McKeown (2014, Experiment 2) asked participants to compare two abstract complex tones varying in timbre.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, at least for verbal memoranda, whether or not memory declines over a filled RI depends on the variability of distractor processing (see Figure 7). At the same time, some studies using visual or spatial memoranda have found that extending the duration of the RI impairs memory even in the absence of a concurrent processing task (B3; Lilienthal, Hale, & Myerson, 2014;Mercer & McKeown, 2014;Ricker & Cowan, 2010).…”
Section: Round B: Retention Interval and Distractor Processingmentioning
confidence: 99%
“…First, there is strong evidence that at least verbal contents of working memory do not decay (Lewandowsky et al, 2009;Oberauer & Lewandowsky, 2013, 2014. Second, findings that are often cited in support of decay for non-verbal materials -a modest decline of accuracy over several seconds -imply a decay rate much too slow for clearing out working memory at the pace at which our stream of consciousness progresses (McKeown & Mercer, 2012;Mercer & Duffy, 2015;Mercer & McKeown, 2014;Ricker & Cowan, 2010;Ricker, Spiegel, & Cowan, 2014;Zhang & Luck, 2009). Working memory could not function as well as it does without removing outdated information, and the present experiments confirm a role for removal of distractors in keeping working memory working.…”
Section: Distractor Removalmentioning
confidence: 99%